The Winning Streak Mark II: How the World's Most Successful Companies Stay on Top Through Today's Turbulent Times - Goldsmith, Walter (London Orion Business Books, 1997)
When The Winning Streak was published in 1984 it was a runaway, and has remainedone of the most respected and referred-to management books. Now the same team of authors have written the management book for the 1990s. Combining their research insights fromThe Winning Streak with the lessons learnt since then, the emphasis this time is on how companies stay on top.
Age Group: Adult
Includes bibliographical references and index
First ed.: George Weidenfeld & Nicolson, 1984